Peer review of Pubfair framework - Morrison, Heather (Université d'Ottawa | University of Ottawa, 2019)
“Science” is only one type of knowledge. There are nine faculties at the University of Ottawa; only one is named “science”, and this is typical at a large university. I strongly recommend replacing “science”, “scientists” and “open science” with more inclusive terminology such as “open scholarship” or “open knowledge”, “scholar” or “researcher” in the title and throughout the document. The Pubfair framework is an excellent beginning for a needed profound transformation in how scholars work together and disseminate research. This is the kind of approach most likely to achieve significant savings based on current spend on scholarly publishing, and these savings will be needed to support innovation in scholarly production and dissemination. My recommendation is to proceed with an iterative approach and an initial focus on helping scholarly communities with unmet needs for new forms of review and publishing, such as scholars who create and share datasets or tools using artificial intelligence, digital humanists, and scholarly bloggers. The specific needs for community input whether through review or collaboration in the planning process will vary by discipline and type of product. The work of defining needs and identifying potential solutions should be led by the scholarly community in consultation with repository managers. This is a reversal of the proposed leadership / consultation approach in the framework document. Finally, while I recommend an immediate start to this approach, my advice is to see this as a long-term radical transformation that will likely take decades to complete.
Keywords: open access; scholarly publishing; scholarly blogs; digital humanities; artificial intelligence; open research data